2023
DOI: 10.1007/s00428-023-03702-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnostics tailoring personalized cancer therapy—an oncologist’s view

Jakob M. Riedl,
Florian Moik,
Tamara Esterl
et al.

Abstract: Medical oncology is rapidly evolving with the implementation of personalized, targeted therapies. Advances in molecular diagnostics and the biologic understanding of cancer pathophysiology led to the identification of specific genetic alterations as drivers of cancer progression. Further, improvements in drug development enable the direct interference with these pathways, which allow tailoring personalized treatments based on a distinct molecular characterization of tumors. Thereby, we are currently experienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In the era of precision medicine, the individualization of investigations/therapy by considering clinicopathological and immunohistochemical factors is of utmost importance in treatment decision-making [45]. The NCCN and ESMO guidelines acknowledge that [ 18 F]FDG PET/CT is useful in equivocal cases as well as in identifying unsuspected regional or distant metastases.…”
Section: The Role Of [ 18 F]fdg Pet/ct In Breast Cancer Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the era of precision medicine, the individualization of investigations/therapy by considering clinicopathological and immunohistochemical factors is of utmost importance in treatment decision-making [45]. The NCCN and ESMO guidelines acknowledge that [ 18 F]FDG PET/CT is useful in equivocal cases as well as in identifying unsuspected regional or distant metastases.…”
Section: The Role Of [ 18 F]fdg Pet/ct In Breast Cancer Stagingmentioning
confidence: 99%
“…The guidelines are not one-size-fits-all; they should be interpreted in the context of a riskstratified/pre-test probability approach by considering other patient factors. This may reduce the incidence of patients undergoing suboptimal or futile invasive therapies which may result in less-than-ideal results [45]. Although [ 18 F]FDG PET/CT is not advised in stage II breast cancers, unsuspected metastases have been detected on [ 18 F]FDG PET/CT.…”
Section: The Role Of [ 18 F]fdg Pet/ct In Breast Cancer Stagingmentioning
confidence: 99%
“…Forrest et al [45] identified INI1 deficiency in pediatric cancers, offering a comprehensive understanding of the genomic and immunologic landscape of INI1-deficient chordomas. This revelation is paramount for tailoring targeted interventions to the unique molecular profiles of individual patients, ushering in an era of precision medicine for chordoma therapy [46]. The study by Forrest et al [45] delves into the intricate genomic and immunologic characterization of INI1-deficient pediatric cancers, unraveling the complexities of this specific subset of chordomas.…”
Section: Genomic Insights Informing Targeted Approachesmentioning
confidence: 99%
“…The insufficient treatment response may be due to the heterogeneity of cancers, which is also associated with CSC biology [2,13]. Thus, the main purpose of stratified medicine is to translate the molecular status of tumour cells into predictive and prognostic indexes that can be applied to personalise treatments leading to longer survival and reduced toxicity [10,14]. In this line, patients who are stratified as high risk for relapse could be treated with adjuvant mode, while patients without detectable CSCs after neoadjuvant treatment and surgery might be adequate for less intensive follow-up procedures.…”
Section: Introductionmentioning
confidence: 99%